Elucidating the impact of gas transport on high-performing air electrodes: a 1D physically based model unveiling the correlation between microstructure and impedance response - Davide Cademartori; Antonio Maria Asensio; Davide Clematis; Maxime Hubert; Jérome Laurencin; Antonio Barbucci (JPhys Energy)
A 1D physically based model of high-performing air electrodes for solid oxide cells is used to unravel the physical mechanisms lying behind the resistive peaks observed in experimental impedance data, posing particular attention to the low-frequency contribution. In particular, the latter is commonly observed when analyzing the impedance response of high-performing air electrode materials, but its physical interpretation is still questioned. The model construction is grounded on the microstructural characteristics of conventional screen-printed electrodes. These properties were extracted by combining the statistical analysis of experimental 2D images taken with a scanning electron microscope with a validated microstructural model able to generate synthetic 3D reconstructions of homogeneous electrode architectures. The implemented electrochemical model is tailored to the specific characteristics of a reference high-performing SmBa _0.8 Ca _0.2 Co _2 O _5+ _δ electrode material. Specifically, the model was used to reproduce its stationary and dynamic behavior in the temperature range 650 °C and 750 °C, with an inlet oxygen partial pressure from 0.1–1 atm. The performed simulations unravel the physical mechanisms lying behind the resistive contributions emerging from the impedance data. In particular, the effect of gas transport is analyzed in detail to understand the impact of the electrode microstructure on its electrochemical behavior. A sensitivity analysis of the effective gas diffusion coefficient highlighted that, in the investigated operating conditions, the electrochemical performance of classic screen-printed air electrodes is not limited by the gas diffusion. In contrast, the low-frequency contribution evidenced in the Nyquist plot was addressed to the impact of gas conversion. The developed electrochemical model successfully completes the correlation between microstructural and electrochemical properties and the results included in this study can be extended to different electrode materials tested in similar operating conditions.